PERFORMANCE MONITORING AND LEARNING-PROGRESS INTERVIEWS - Risbayeva Luna Askanbay qizi; Zoyirova Dilfuza Xayriddinovna (TADQIQOTLAR, 2026)
Annotation: According to the specifications of the educational standards for Secondary School certification (Level I), on the one hand the modes of performance monitoring correlate with the traditi onal formulation of tasks. On the other hand, they need to correlate with internationally used test formats which are based on the Common European Framework of Reference for Languages, on the IQB proposals and on the standards of international language certificates (Müller-Hartmann et al. 2013). For the field of listening –, hearing/seeing – and reading comprehension we recommend formats like multiple choice, clozes, matching tasks or tasks for the analysis or structuring of text statements. In order to evaluate the learning development regarding the productive communication competencies (speaking and writing) and the linguistic mediation it is recommended to perform receptive interviews or assign tasks in which the students present statements and opinions, write descriptions, organise information or give comments.